An efficient method based on an inhibitor–enzyme complex to screen an active compound against lipase from Toona sinensis. Issue 21 (7th October 2021) - Wang, Yunxiao; Wang, Jifeng; Wang, Shunxin; Cao, Zengyuan; Gu, Dongyu; Wang, Yi; Tian, Jing; Yang, Yi
Abstract : As a popular vegetable, Toona sinensis has a wide range of bioactivities including lipase inhibitory activity. Abstract : As a popular vegetable, Toona sinensis has a wide range of bioactivities including lipase inhibitory activity. In the present study, an efficient and rapid method using a ligand–enzyme complex was established for screening of an active compound against lipase from Toona sinensis . The ethyl acetate extract of Toona sinensis showed good lipase inhibitory activity. After incubation with lipase, one of the compounds in the extract decreased significantly while comparing the HPLC chromatograms before and after incubation, which indicated that it may be the active compound bound to lipase. Then, the compound was isolated using a Sephadex LH-20 column and identified as 1, 2, 3, 4, 6-penta- O -galloyl-β-d -glucose. The in vitro activity test showed that the compound had good inhibitory activity against lipase, and its IC50 value was 118.8 ± 1.53 μg mL −1 . The kinetic experiments indicated that 1, 2, 3, 4, 6-penta- O -galloyl-β-d -glucose inhibited lipase through mixed competitive and non-competitive inhibitions. Further docking results showed that the target compound could bind to the active site of lipase stably through seven hydrogen bonds, resulting in a docking energy of −8.31 kcal mol −1 . The proposed method can not only screen the lipase inhibitors from Toona sinensis quickly and effectively, but also provide an effective way for the rapid screening of active substances in natural food and plants.